ANALISIS KERJASAMA PEMERINTAHAN REGIONAL DIY DAN KYOTO: SEKARANG DAN MASA MENDATANG - Alfarisi, Habib (Universitas Panca Marga, 2021)
Paradiplomacy is a diplomatic relationship carried out by non-state actors. Paradiplomacy is one part of international relations in the modern era, and that international relations in the present era is not state-centric or centered only on the state, but also on non-state actors such as individuals or even local governments. The cooperation between Kyoto Prefecture and the government of the Special Region of Yogyakarta is one form of paradiplomacy, which is called the Sister City. Sister Province itself is a collaboration either engaged in politics or economics or both carried out between two regional governments that have the same problems and views and the cooperation carried out is aimed at solving problems that exist between the two cities. The cooperation between the Special Region of Yogyakarta and Kyoto is one of the Sister Province collaborations which is said to be quite productive and produces many things that benefit both parties. In this paper, the author will try to explain the cooperation carried out by the two parties in detail and explain the past and future that can be done by both parties involved in the cooperation. The author uses data from 2015-2020. The author assumes that the Sister City cooperation between DIY and Kyoto produces many productive things. The author uses a descriptive-analytic method. Keywords : Sister Province, Yogyakarta, Kyoto, Paradiplomacy, Transnational